Polyaniline Nanorods Grown on Hollow Carbon Fibers as High‐Performance Supercapacitor Electrodes. Issue 7 (30th May 2016) - Gao, Shuangyan; He, Shuyue; Zang, Peiyu; Dang, Liqin; Shi, Feng; Xu, Hua; Liu, Zonghuai; Lei, Zhibin
Abstract: Hollow carbon fibers (aCFs) with a high specific surface area are applied as conductive scaffolds for polyaniline (PANi) growth. aCFs oxidized by HNO3 treatment have more surface negative charges, which interact with protonated aniline molecules in acidic media. The subsequent chemical oxidative polymerization assisted by (NH4 )2 S2 O8 yields aCF–PANi composites with PANi nanorod arrays strongly coupled on both the external and internal surfaces of the aCFs. Serving as binder‐free supercapacitor electrode, the aCF–PANi composite with 31 wt % PANi exhibits a specific capacitance of 364 F g −1, and retains 70 % of this value at 20 A g −1 . More interestingly, it exhibits excellent cycling stability with 92.5 % capacitance retention, and outstanding reversibility with 98.6 % coulombic efficiency, even after 5000 continuous cycles; this performance is far superior to that of both aCF and PANi electrodes. The strongly coupled PANi arrays on the aCF surface greatly reduce the interface resistance, thus facilitating both ion and electron transport for enhanced capacitive performance. Abstract : Keep cycling ! Conductive hollow carbon fibers (aCF) oxidized with HNO3 interact with protonated aniline molecules through π–π stacking or hydrogen bonding to strongly couple with polyaniline (PANi) to form uniform nanorod arrays. As a binder‐free supercapacitor electrode, an aCF–PANi composite exhibits high specific capacitance, good rate capability, remarkable cycling stability, and reversibility with 92.5 % capacitance retention and 98.6 % coulombic efficiency, even after 5000 cycles.